Symplocos retusa (Symplocaceae), una nueva especie de Costa Rica - Kriebel, Ricardo; González, José; Alfaro, Evelio (Lankesteriana: International Journal on Orchidology, 2016)
Symplocos retusa, a new species restricted to the wet forests of the Pacific slope of the Talamanca range in Costa Rica is described, illustrated, and compared to its closest presumed relative. Symplocos retusa is distinguished by its entire leaf blades with a conspicuous retuse apex; purple, pentamer- ous, pedicellate, solitary, axillary flowers subtended by deciduous bracts; fruit apex flat and distended beyond the point of calyx lobe attachment. It is compared to S. tribracteolata Almeda, another Costa Rican endemic with solitary, pedicellate, white to pink hexamerous flowers and serrulate or crenate leaf blades with acuminate apex.